1975
DOI: 10.1213/00000539-197507000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cocaine Administration on Halothane MAC in Dogs

Abstract: Intravenous cocaine (2 mg/kg or 4 mg/kg) was associated with a dose-dependent increase of halothane MAC in the dog. The largest increase in halothane MAC was from 1.06 plus or minus 0.03 to 1.35 plus or minus 0.04 vol/100 ml 3 hours after 4 mg/kg of cocaine. Halothane MAC 24 hours following a single administration of either 2 mg/kg or 4 mg/kg of cocaine or after 10 daily doses of 4 mg/kg of cocaine was near control MAC. These data support the speculation that increased central nervous system catecholamine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…For example, drugs that increase catecholamine release in the CNS, such as cocaine, increase MAC during acute intoxication . Canine studies demonstrated a dose‐dependent increase of MAC for halothane following acute cocaine administration . In contrast, chronic cocaine exposure is associated with a decrease in MAC for isoflurane .…”
Section: Factors That Affect Macsupporting
confidence: 74%
“…For example, drugs that increase catecholamine release in the CNS, such as cocaine, increase MAC during acute intoxication . Canine studies demonstrated a dose‐dependent increase of MAC for halothane following acute cocaine administration . In contrast, chronic cocaine exposure is associated with a decrease in MAC for isoflurane .…”
Section: Factors That Affect Macsupporting
confidence: 74%
“…On the other hand, drugs that increase norepinephrine levels cause an increase in the requirement for inhalation anesthetics. Similarly, it has been reported that acute administration of amphetamine [ 23 ] and cocaine [ 24 ] increases the MAC of halothane in dogs due to an increase in the catecholamine concentration in the central nervous system.…”
Section: Discussionmentioning
confidence: 89%
“…The excess of neurotransmitter in the synaptic cleft of cerebral neurons of the limbic system produces the euphoric effects of cocaine. The stimulant effect on the CNS may lead to an increase in minimal alveolar concentration (MAC) of inhaled anaesthetic drugs (Stoelting et al 1975). An important finding in relation to everyday practice is that intranasal administration of cocaine near the dose used for topical anaesthesia causes vasoconstriction of the coronary arteries with a decrease in the coronary blood flow, despite an increase in myocardial oxygen demand (Lange et al 1989).…”
Section: Malignant Hyperthermiamentioning
confidence: 99%